Rancang Bangun Alat Pengukur Jarak Tempuh Lari Laun Menggunakan Sensor Inertial Measurement Unit (IMU) Berbasis Mikrokontroler - Yunidar Yunidar; Yazid Yaskur; Roslidar Roslidar; Mohd. Syaryadhi (Jurnal Rekayasa Elektrika, 2022)
Jogging is a form of trotting or running at a slow or leisurely pace. So far, the measurement of running distance is determined by wearables Global Positioning System (GPS) and pedometers. The use of wearables with GPS commonly used by joggers cannot be used in indoor conditions. In addition, the use of a pedometer for measuring the number of steps cannot calculate the specific distance due to the inconsistency of human footsteps. This study aims to design a device to measure the distance traveled in jogging. To measure the distance traveled in a run, an Inertial Measurement Unit (IMU) sensor can be used with a linear acceleration output then reduce the measurement noise by using a Kalman Filter. The acceleration signal is processed into a velocity signal and the velocity signal is processed into a distance signal through integration. From the results of the prototype design, it is able to measure a distance of 25m with an error of 0.78%, a distance of 50m with 0.53% and a distance of 75m with 0.22%.